Unsettling sovereignty: Violence, myths and the politics of history in the Ethiopian Somali metropolis. (October 2021) - Emmenegger, Rony
Abstract: An increasingly consolidated anthropological scholarship has moved from a legal notion of sovereignty towards an analysis of its violent enactment. Yet, it has paid insufficient attention to the ways in which the idea of sovereignty forms and operates in localized political struggles. Taking seriously Bonilla's (2017) call for the "unsettling" of sovereignty, this article scrutinizes how ideas of legitimate rule have formed around myths of violence in the capital of the Ethiopian Somali region. It uses ethnographic material to examine the politics of history around material constructions through which myths of violence are entangled with the city's landscape of memory. It reveals sovereignty in the process of formation, becoming culturally and materially grounded in the myths of violence of an emerging Somali nation within the ethnic federal Ethiopian state. This article argues that past claims to sovereignty continue to affect the politics of history, with profound consequences for ongoing nation-state building projects and the corresponding territorial imaginations. It thus highlights the inherently fragile nature of ideas of state sovereignty in the frontier metropolis. On this basis, it contributes to a geographically differentiated anthropology of sovereignty and to an understanding of its co-constitution through violence in the frontier and myths in the metropolis. Highlights: The idea of sovereignty requires critical interrogation. Ideas of state sovereignty emerge and consolidate in localized political struggles. The metropolis constitutes a specific sphere of influence within the frontier. The politics of history anchors ideas of sovereignty in reference to the past. Landscapes of memory entangle nation-state mythologies culturally and materially.